2018
DOI: 10.1038/s41598-018-33530-8
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of brain development in school-age children born preterm with very low birth weight

Abstract: Preterm birth (gestational age < 37 weeks) with very low birth weight (VLBW, birth weight ≤ 1500 g) is associated with lifelong cognitive deficits, including in executive function, and persistent alterations in cortical and subcortical structures. However, it remains unclear whether “catch-up” growth is possible in the preterm/VLBW brain. Longitudinal structural MRI was conducted with children born preterm with VLBW (n = 41) and term-born peers participating in the Norwegian Mother and Child Cohort Study (MoBa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 129 publications
14
42
1
Order By: Relevance
“…In our multicentre cohort of VPT infants, cortical maturation metrics at TEA, especially selected metrics of surface area and inner cortical curvature, were independent biomarkers of future intellectual and linguistic ability. Cortical surface area in almost every region of the VPT cortex was positively correlated with cognitive and language scores, which validates and extends previous published findings 7 8 10. Curvature was negatively correlated with cognitive and language scores for large swaths of the brain, and this metric explained a greater amount of variability in Bayley scores than cortical surface area.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our multicentre cohort of VPT infants, cortical maturation metrics at TEA, especially selected metrics of surface area and inner cortical curvature, were independent biomarkers of future intellectual and linguistic ability. Cortical surface area in almost every region of the VPT cortex was positively correlated with cognitive and language scores, which validates and extends previous published findings 7 8 10. Curvature was negatively correlated with cognitive and language scores for large swaths of the brain, and this metric explained a greater amount of variability in Bayley scores than cortical surface area.…”
Section: Discussionsupporting
confidence: 90%
“…Decreased cortical surface area is a well-established consequence of prematurity 7–13. In this cohort, surface area of nearly every region of the preterm brain correlated positively with cognitive ability, corroborating prior studies 7–10.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The underlying reason may be maturational delay of brain structures, specifically white matter tracts. In fact, MRI studies of preterm children and full-term controls found that brain development in both groups follows a similar trajectory that is delayed for children who were born preterm (Sripada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%